2020
DOI: 10.1038/s41598-020-68466-5
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour versus clinic blood pressure levels as predictors of long-term cardiovascular and renal disease outcomes among African Americans

Abstract: In Caucasian and Asian populations, evidence suggests that 24-h blood pressures (BP) are more predictive of long-term cardiovascular events than clinic BP. However, few long-term studies have evaluated the predictive value of 24-h BP phenotypes (24-h, daytime, nighttime) among African Americans (AA). The purpose of this study is to evaluate the added value of 24-h BP phenotypes compared to clinic BP in predicting the subsequent fatal and non-fatal cardiovascular/renal disease events in AA subjects. AA subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…With regard to the time of day that is most predictive of adverse health outcomes in relation to the ambulatory BP, studies in patients 3 , 5 8 and populations 10 , 11 , 22 showed that the nighttime BP by far outperformed the daytime BP, although it should be confirmed in other ethnics. 32 In a substudy of the Systolic Hypertension in Europe Trial, 5 808 patients were randomized in a double-blind manner to placebo or active BP-lowering treatment. The nighttime systolic BP (midnight to 6 am ) was the most accurate predictor of end points.…”
Section: The Diurnal Bp Profilementioning
confidence: 99%
“…With regard to the time of day that is most predictive of adverse health outcomes in relation to the ambulatory BP, studies in patients 3 , 5 8 and populations 10 , 11 , 22 showed that the nighttime BP by far outperformed the daytime BP, although it should be confirmed in other ethnics. 32 In a substudy of the Systolic Hypertension in Europe Trial, 5 808 patients were randomized in a double-blind manner to placebo or active BP-lowering treatment. The nighttime systolic BP (midnight to 6 am ) was the most accurate predictor of end points.…”
Section: The Diurnal Bp Profilementioning
confidence: 99%
“…Several published articles were supported by this SFRN with several additional abstracts containing data that we plan to publish in the future. 6–13 Investigators were able to adhere to the hypotheses proposed with no major changes due to innovative ideas in implementation of the projects. In the basic science project, changes were observed in DNA methylation and gene expression in T lymphocytes (T cells) of Dahl salt-sensitive rats fed different diets, 6,7 providing new insight into the mechanisms by which immune mechanisms amplify salt-sensitive hypertension and renal damage.…”
Section: Our Experiencementioning
confidence: 99%
“…8 In addition, it was observed that in Black people, 24-hour BP monitoring provides limited added value as a predictor of cardiovascular/renal disease events. 10 SFRN enabled postdoctoral fellows to participate in multiple types of research and learn how basic and clinical studies are conducted and strengths and limitations of each (Table 1). In addition to specific successes in each of the projects, The MCW Center also made critical methodological advances in the realm of methylation sequencing and analyses.…”
Section: Our Experiencementioning
confidence: 99%